Human Benefit through the Diffusion of Information Systems Design Science Research c - Pries-Heje, Jan.; Venable, John.; Bunker, Deborah; Russo, Nancy L.; DeGross, Janice I.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the IFIP WG 8.2/8.6 International Working Conference on Human Benefit through the Diffusion of Information Systems Design Science Research, held in Perth, Australia, in April 2010. The 19 revised research papers presented together with 3 panel papers were carefully reviewed and selected from 45 submissions. The papers, preceded by an introductory chapter, are divided in topical sections on design, organizations, and adoption; design exemplars; human benefit; designing adoption; design science; and participation in design.
Creation, Transfer, and Diffusion of Innovation in Organizations and Society: Information Systems Design Science Research for Human Benefit -- Creation, Transfer, and Diffusion of Innovation in Organizations and Society: Information Systems Design Science Research for Human Benefit -- 1: Design, Organizations, and Adoption -- Incommensurability and Multi-paradigm Grounding in Design Science Research: Implications for Creating Knowledge -- The Design and Engineering of Mobile Data Services: Developing an Ontology Based on Business Model Thinking -- The Role of Social Networks in Early Adoption of Mobile Devices -- 2: Design Exemplars -- Roles in Innovative Software Teams: A Design Experiment -- A Case Study of Improving Information Technology Governance in a University Context -- Extending Design Science Research Methodology for a Multicultural World -- 3: Human Benefit? -- The Reality of Rhetoric in Information Systems Adoption: A Case Study Investigation of the Uk National Health Service -- Social Consequences of Nomadic Working: A Case Study in an Organization -- Design Science Research for Business Process Design: Organizational Transition at Intersport Sweden -- 4: Designing Adoption -- An Adoption Diffusion Model of RFID-Based Livestock Management System in Australia -- Developing a Broadband Adoption Model in the UK Context -- The Uneven Diffusion of Collaborative Technology in a Large Organization -- Toward an Understanding of the Evolution of IFIP WG 8.6 Research -- 5: Design Science -- Functional Service Domain Architecture Management: Building the Foundation for Situational Method Engineering -- Management Design Theories -- Modeling Forensic Evidence Systems Using Design Science -- 6: Participation in Design -- Participatory Design Activities and Agile Software Development -- Participation in Living Lab: Designing Systems with Users -- Manufacturing Accomplices: ICT Use in Securing the Safety State at Airports -- 7: Panels -- A Brief History of IFIP WG 8.2 Research: The People, the Places, the Methods, and the Issues -- The Role of Public Policy in Enhancing the Design and Diffusion of Information Systems and Technology for Human Benefit -- Opening up the Agile Innovation Process.
Keywords: Computer science; Software engineering; Information theory; Information systems; Database management; Information storage and retrieval systems; Computer Science; Theory of Computation; Database Management; Information Storage and Retrieval; Information Systems Applications (incl.Internet).; Software Engineering/Programming and Operating Systems; Information Systems and Communication Service